Deep Learning for Automatic Segmentation of Oral and Oropharyngeal Cancer Using Narrow Band Imaging: Preliminary Experience in a Clinical Perspective - Paderno, Alberto; Piazza, Cesare; Del Bon, Francesca; Lancini, Davide; Tanagli, Stefano; Deganello, Alberto; Peretti, Giorgio; De Momi, Elena; Patrini, Ilaria; Ruperti, Michela; Mattos, Leonardo S.; Moccia, Sara (Frontiers in Oncology, 2021)
Introduction: Fully convoluted neural networks (FCNN) applied to video-analysis are of particular interest in the field of head and neck oncology, given that endoscopic examination is a crucial step in diagnosis, staging, and follow-up of patients affected by upper aero-digestive tract cancers. The aim of this study was to test FCNN-based methods for semantic segmentation of squamous cell carcinoma (SCC) of the oral cavity (OC) and oropharynx (OP). Materials and Methods: Two datasets were retrieved from the institutional registry of a tertiary academic hospital analyzing 34 and 45 NBI endoscopic videos of OC and OP lesions, respectively. The dataset referring to the OC was composed of 110 frames, while 116 frames composed the OP dataset. Three FCNNs (U-Net, U-Net 3, and ResNet) were investigated to segment the neoplastic images. FCNNs performance was evaluated for each tested network and compared to the gold standard, represented by the manual annotation performed by expert clinicians. Results: For FCNN-based segmentation of the OC dataset, the best results in terms of Dice Similarity Coefficient (Dsc) were achieved by ResNet with 5(×2) blocks and 16 filters, with a median value of 0.6559. In FCNN-based segmentation for the OP dataset, the best results in terms of Dsc were achieved by ResNet with 4(×2) blocks and 16 filters, with a median value of 0.7603. All tested FCNNs presented very high values of variance, leading to very low values of minima for all metrics evaluated. Conclusions: FCNNs have promising potential in the analysis and segmentation of OC and OP videoendoscopic images. Image quality is essential in the training phase of the algorithms, with a particular focus on illumination and color balance. Future prospective studies should assess and optimize these variables through accurate planning and data collection.